Fast compact true random number generator based on multiple sampling. Issue 13 (1st June 2017) - Choi, P.; Lee, M.‐K.; Kim, D.K.
Abstract : A new ring‐oscillator‐based true random number generator (RNG) based on multiple sampling is proposed. The proposed generator uses the outputs of all gates in a ring oscillator, as positive‐ and negative‐edge clock signals. The generator in two field‐programmable gate array families is implemented, and it is verified that the generated bit sequences pass the RNG tests of the National Institute of Standards and Technology. The experimental results show that the proposed generator is faster and more compact than the existing ring‐oscillator‐based true RNGs.